Occurrence and Risk Factors of Cryptosporidium parvum among Immunocompromised Patients in Ibb City - Yemen - Qasem, Eglal Ahmed; Al-Shehari, Wadee Abdullah; Al-Shamahy, Hassan AbdAlwahab; Edrees, Wadhah Hassan; Al-Awar, Mohammed Sadeq (Journal of medical and pharmaceutical sciences, 2022)
Cryptosporidium parasite is causing opportunistic Cryptosporidiosis diseases among Immunocompromised patients that lead to acute and persistent diarrhea and health complications, especially in developing countries. This study amid to determine the occurrence of C. parvum among immunocompromised patients presenting at Al- Thawra hospital in Ibb city- Yemen. Sample of the study (87) stool specimens were collected between November 2016 and July 2017. The stool specimens were screened for the C. parvum by using formalin- ether concentration, Ziehl- Neelsen methods, and enzyme- linked immunosorbent assay (ELISA). The required data were obtained by a designed questionnaire. The result revealed that the overall rate of C. parvum was 62 (71.26%) observed among immunocompromised patients and both males and females had nearly equal frequency rates of infection. The highest rate of infection was 80% reported within age less than 10 years and 78.3% among patients who coming from the rural area. Also, it was found 83.33% of infected patients drinking from piped water with significant difference (P<0.05). In addition, 73.81% of individuals contacting animals were positive for infection. The most frequent rate of infection was 53.2% recorded for chronic renal failure, 42% for malignancy, and 4.8% for renal transplant patients. The clinical features most frequently presented were diarrhea, malaise, poor appetite, weight loss, abdominal pain, and fever. Similarly, 90.3% and 97.8% of cases were suffered from semi- liquid diarrhea and acute diarrhea, respectively. Recommendation as described in this study health education programs are needed for preventing and controlling the transmission of Cryptosporidium parasites among weak immune individuals.